Manipulation of protein translation and stem cell self-renewal by CRISPR activation of rRNA transcription - Maximilian Wiesbeck; Emilie L. Alard; Florencia Merino; Niti Chowdhury; Luisa Egert; Anna Danese; Simon Imhof; Matilde Iraci Borgia; Akshaya Rajan; Nadine Fernandez-Novel Marx; Edina Kepesidis; Anna Köferle; et al. (Science, 2026)
Ribosomal RNA (rRNA) transcription rates vary during development, and their dysregulation is linked to diseases such as cancer and ribosomopathies. Owing to their high abundance and genomic redundancy, the functional significance of rRNA-levels remains unclear. Here, we developed TAPIR (Targeted Activation of Protein Translation), a CRISPR-based approach to elevate rRNA-levels by inducing 47S rDNA transcription. TAPIR increased nucleolar size and enhanced protein synthesis, even in rapidly proliferating cells. In neural stem cells, elevated translation promoted self-renewal and proliferation in vitro and in vivo. Furthermore, TAPIR enabled the modeling and partial rescue of associated disease phenotypes. Our findings revealed that rRNA-levels directly regulate translational output and that protein synthesis capacity can act as a key determinant of mammalian stem cell behavior.